Proteomic analysis of granulomas from cattle and pigs naturally infected with Mycobacterium tuberculosis complex by MALDI imaging - Larenas-Muñoz, Fernanda; Sánchez-Carvajal, José María; Ruedas-Torres, Inés; Álvarez-Delgado, Carmen; Fristiková, Karola; Pallarés, Francisco José; Carrasco, Librado; Chicano-Gálvez, Eduardo; Rodríguez-Gómez, Irene Magdalena; Gómez-Laguna, Jaime (Frontiers in Immunology, 2024)
Matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) has recently gained prominence for its ability to provide molecular and spatial information in tissue sections. This technology has the potential to uncover novel insights into proteins and other molecules in biological and immunological pathways activated along diseases with a complex host-pathogen interaction, such as animal tuberculosis. Thus, the present study conducted a data analysis of protein signature in granulomas of cattle and pigs naturally infected with Mycobacterium tuberculosis complex (MTC), identifying biological and immunological signaling pathways activated throughout the disease. Lymph nodes from four pigs and four cattle, positive for MTC by bacteriological culture and/or real-time PCR, were processed for histopathological examination and MALDI-MSI. Protein identities were assigned using the MaTisse database, and protein-protein interaction networks were visualized using the STRING database. Gene Ontology (GO) analysis was carried out to determine biological and immunological signaling pathways in which these proteins could participate together with KEGG analysis. Distinct proteomic profiles between cattle and pig granulomas were displayed. Noteworthy, the GO analysis revealed also common pathways among both species, such as "Complement activation, alternative pathway" and "Tricarboxylic acid cycle", which highlights pathways that are conserved among different species infected by MTC. In addition, species-specific terms were identified in the current study, such as "Natural killer cell degranulation" in cattle or those related to platelet and neutrophils recruitment and activation in pigs. Overall, this study provides insights into the immunopathogenesis of tuberculosis in cattle and pigs, opening new areas of research and highlighting the importance, among others, of the complement activation pathway and the regulation of natural killer cell and neutrophil-mediated immunity in this disease.Revisiting tuberculous granuloma by MALDI-Imaging